THE USE OF SMARTPHONES IN PHYSICAL LEARNING ON SOUND WAVES - Jalis Putri, Yunita Jeliyah; Desnita, Desnita (Department of Physics Universitas Negeri Padang, 2024)
The role of education is very important to prepare students who have knowledge and skills in using technology. Physics learning in the 21st century requires teachers to make technology an efficient and innovative learning medium. One technology that is often used by students is a smartphone. Smartphones are a technology that can be used to motivate and motivate students' curiosity to learn. The purpose of this study is to see the use of smartphones in learning physics, especially sound wave material. This type of research is descriptive qualitative research. Research data were collected through questionnaires and interview sheets. Questionnaires are distributed using a rating scale. Price data is processed using a proportion technique. The results of this research are that on average students in five public senior high schools already have a smartphone. Smartphones have been used in learning. However, the use of smartphones is still limited. Smartphones have not been used as learning media in sound wave experiment activities. In addition, smartphones are more often used by students to play social media than studying. This shows that the use of smartphones by teachers and students has not been carried out optimally in learning physics, especially sound wave material.